Effectiveness of combined problem-based learning and flipped classroom strategies in teaching a medical-surgical nursing course - Dhawo, Maria Silvana; Sana, Erlyn A. (Manila The National Teacher Training Center for the Health Professions, 2017)
Sekolah Tinggi Ilmu Kesehatan (STIKES) Suaka Insan Banjarmasin has been using problem based learning (PBL) as an innovative teaching strategy since 2012. However, problems in PBL implementation among the students presented as a barrier to achieve the goals for 21st century nursing education in Indonesia. Hence, the nurse educators in STIKES Suaka Insan plan to apply another teaching strategy and combine it with PBL. The said teaching strategy is flipped classroom. This study compared the effectiveness of PBL and the flipped PBL (FPBL) strategies on students? academic achievement, independent learning, and critical thinking skill, determined the students? perceptions on their experience using the FPBL strategies; and determined the strengths an weaknesses of the FPBL. This study used a combination of experimental and descriptive qualitative research design, involved 2 groups totaling 84 students divided by fishbowl method into non-experimental group (PBL) and experimental group (FPBL). The study administered a written test examination, concept map presentation, quantitative and qualitative survey to measure students? achievement, independent learning, critical thinking skill and perception. The mean score for PBL group was 34.17 for MCQ and for extended essay questions was 37.71. The mean score for the FPBL in the MCQs was 36.67 and for extended essay questions was 40.38. In terms of independent learning, the mean score for PBL was 60.19 and FPBL was 73.60. The students? competency in critical thinking aspect was 59.19 for PBL and 71.10 for FPBL. The students have a positive perception towards FPBL. The findings provided the option for the nurse educators in STIKES Suaka Insan to develop the transformative learning strategy by implementing the new teaching method. These findings contribute to the growth of research on problem based learning and a flipped classroom.
Thesis (Master of Health Professions Education)--University of the Philippines Manila, May 2017
Panel Members: Erlyn A. Sana PhD, Chair/Adviser; Nemuel S. Fajutagana MD MHPEd, Reader/Critic; Jesus N. Sarol Jr. PhD, Member; Melflor A. Atienza MD MHPEd, Member; Maria Elizabeth M. Grageda PTRP MHPEd, Member.
Keywords: Problem-based learning; Flipped classrooms